2022
DOI: 10.1021/acsami.1c23429
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Targeted Hydroxychloroquine Nanotherapeutics for Rheumatoid Arthritis Therapy

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease with unclear pathogenesis. Hydroxychloroquine (HCQ), despite its moderate anti-RA efficacy, is among the few clinical drugs used for RA therapy. Macrophages reportedly play a vital role in RA. Here, we designed and explored macrophage-targeted HCQ nanotherapeutics based on mannose-functionalized polymersomes (MP-HCQ) for RA therapy. Notably, MP-HCQ exhibited favorable properties of less than 50 nm size, glutathione-accelerated HCQ release, and M1 phenotype mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 57 publications
(107 reference statements)
1
22
0
Order By: Relevance
“…In addition, inducing anti-inflammatory M2 macrophages, inhibiting the production of inflammatory factors and alleviating synovitis of RA are also the focus of current research. This is consistent with our experimental results [ 20 ]. Enrichment analysis also showed that cellular immune processes such as B cells differentiation, T cells proliferation, cell adhesion, cell chemotaxis and endocytosis were involved in the pathogenesis of RA.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, inducing anti-inflammatory M2 macrophages, inhibiting the production of inflammatory factors and alleviating synovitis of RA are also the focus of current research. This is consistent with our experimental results [ 20 ]. Enrichment analysis also showed that cellular immune processes such as B cells differentiation, T cells proliferation, cell adhesion, cell chemotaxis and endocytosis were involved in the pathogenesis of RA.…”
Section: Discussionsupporting
confidence: 94%
“…Early intervention, such as TNF blockers, can increase the rate of clinical response and the likehood of clinical symptom improvement ( 35 , 36 ). Additionally, biologics targeting on IL-1, IL-6, IL-10, IL-17 and GM-CSF are also favored by researchers, and relevant clinical trials are underway ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Meanwhile, the advantage of nanomaterial targeting is that it can target specic target cells, such as tumor cells and macrophages, with effective affinity for therapeutic purposes. 48,49 NPs have been widely reported in the diagnosis and treatment of AP. The purpose of this review is to discuss the clinical implications of the different nanoplatforms that have been published in recent years for the diagnosis and therapy of AP.…”
Section: Introductionmentioning
confidence: 99%